(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Mitotic figure counting is simplest and oldest method for determining proliferative activity of cell. It is considered as one of the important diagnostic aid in cancer pathology. Though advanced methods to evaluate dysplastic features are more precise and definite but expense and time makes them less practicable for routine use. Therefore an effort was made to use economical as well as simple approach involving crystal violet stain (1%) to study the mitotic figures in oral squamous cell carcinoma. Materials and Methods: This descriptive research included samples, consisting of thirty three cases of the oral squamous cell carcinoma (OSCC). Representative sections were stained with H&E stain and 1% crystal violet stain respectively. The stained sections were viewed under optical microscope to count mitotic figures for evaluating the effectiveness of 1% crystal violet stain. Data obtained was statistically analyzed by using sample t-test. Results: There was noteworthy increase in the mean mitotic count among the crystal violet stained sections of OSCC in contrast to the OSCC sections stained with H&E (P = 0.00). Conclusion:1% Crystal violet stain can be considered as one of the optimum stains to observe the mitotic figure. Practice of staining with 1% crystal violet during routine histopathological procedures will be cost effective and may be used as a selective stain.